Manfaat Ekstrak Buah Delima (Punica Granatum L.) Sebagai Zat Aktif dalam Formulasi Sediaan Kosmetika - Andariningtyas Putri Febriati; Firlie Bastia Putty Zahra; Nadya Yundasari; Nia Yuniarsih (Jurnal Health Sains, 2022)
Pomegranate or often known as pomegranate (Punica granatum L) is a fruit belonging to the Punicaceae family which contains anthocyanins. Pomegranates generally have a red color produced by anthocyanin flavonoid compounds or natural color pigments which are usually safe to use as a substitute for synthetic dyes. In Indonesia, there are three types of pomegranate that grow in Indonesia, namely red, white and black pomegranates. The methanol extract in pomegranate plays a role in antioxidant activity while the color pigment in pomegranate can be used as a natural dye in the manufacture of various cosmetics. In this study, the identification of the benefits of pomegranate as a natural ingredient in the manufacture of cosmetics, samples using various journals and articles were reviewed and summarized into a single unit and summarized into a complete journal review.